Multimodal Simulation of a Novel Device for a Safe and Effective External Ventricular Drain Placement - Umana, Giuseppe Emmanuele; Scalia, Gianluca; Yagmurlu, Kaan; Mineo, Rosalia; Di Bella, Simone; Giunta, Matteo; Spitaleri, Angelo; Maugeri, Rosario; Graziano, Francesca; Fricia, Marco; Nicoletti, Giovanni Federico; Tomasi, Santino Ottavio; et al. (Frontiers in Neuroscience, 2021)
Background: External ventricular drain (EVD) placement is mandatory for several pathologies. The misplacement rate of the EVD varies widely in literature, ranging from 12.3% to 60%. The purpose of this simulation study is to provide preliminary data about the possibility of increasing the safety of one of the most common life-saving procedures in neurosurgery by testing a new device for EVD placement. Methods: We used a novel guide for positioning the ventricular catheter (patent RM2014A000376). The trajectory was assessed using 25 anonymized head CT scans. The data sets were used to conduct three-dimensional computer-based and combined navigation and augmented reality-based simulations using plaster models. The data set inclusion criteria were volumetric head CT scan, without midline shift, of patients older than 18. Evans’ index was used to quantify the ventricle’s size. We excluded patients with slit ventricles, midline shift, skull fractures, or complex skull malformations. The proximal end of the device was tested on the cadaver. Results: The cadaveric tests proved that a surgeon could use the device without any external help. The multimodal simulation showed Kakarla grade 1 in all cases but one (grade 2) on both sides, after right and left EVD placement. The mean Evans’ index was 0.28. The geometric principles that explain the device’s efficacy can be summarized by studying the properties of circumference and chord. The contact occurs, for each section considered, at the extreme points of the chord. Its axis, perpendicular to the plane tangent to the spherical surface at the entry point, corresponds to the direction of entry of the catheter guided by the instrument. Conclusions: According to our multimodal simulation on cadavers, 3D computer-based simulation, 3D plaster modeling, 3D neuronavigation, and augmented reality, the device promises to offer safer and effective EVD placement. Further validation in future clinical studies is recommended.